A regulação dos serviços de saneamento em casos latino-americanos - João Gilberto de Souza Ribeiro (2013)
Discussions in water supply and sanitation have a wide range of interrelationship campuses. The development of management, for example, accounts for the planning, the provision, the regulation and social control of water and sanitation services, which often do not prioritize or ignore the fundamental principles such as universality and quality, both necessary for human health. Moreover, the water supply and sanitation field strongly relates to other sectors such as health, economy and environment; hence the importance of the discussion of intersectionality for this area. The research is justified for it contributes elements to the public sanitation policies debate, especially concerning the regulatory process of such services, the reform of which began in the last quarter of the Twentieth Century. This thesis therefore intents to understand the regulatory models that are the expression of the changes over the recent decades in Latin America. The methodological procedures are guided by the techniques of data collection and analysis through the Qualitative Methodology, using relevant documentary sources from 12 regulatory agencies and semi-structured interviews with relevant players in the regulatory process. The Content Analysis aided by computer favored the categorization of data which have been processed by multivariate statistics. It was also noted that the regulatory agencies studied have stronger boundaries of regulatory substance. The technical tools are prioritized over the regulatory governance. It is noteworthy that tariffs and the quality of services as the main parameters observed by regulatory institutions in the study. Furthermore, the results are the expression of a political-institutional framework, which is under construction from new legal frameworks, shaped by the players (managers, politicians and technicians), to enhance the public management. It is believed that these discussions may clarify questions about creating subsidies for greater citizen participation, strengthening the social control over the scheduling of such water supply and sanitation services regulatory institutions.